2013
DOI: 10.1007/s11104-012-1575-y
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen use efficiency (NUE) in rice links to NH4 + toxicity and futile NH4 + cycling in roots

Abstract: + efflux in the root elongation zone, measured by SIET, was nearly sevenfold greater in GD than in W23, and this was coupled to strongly stimulated root respiration. In both cultivars, root growth was affected more severely by high NH 4 + than shoot growth. High NH 4 + mainly inhibited the development of total root length and root area, while the formation of lateral roots was unaffected. Conclusions It is concluded that the larger degree of seedling growth inhibition in low-vs. high-NUE rice genotypes is asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
67
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 54 publications
8
67
1
1
Order By: Relevance
“…This study critically reexamines the nature of futile transmembrane NH 3 /NH 4 + cycling in barley roots, a phenomenon with ties to NH 4 + toxicity in a wide range of higher plants (Feng et al, 1994;Britto et al, 2001bChen et al, 2013 ; Fig. 1A), electroneutral NH 3 transport accounts for the observed rapid rates of 13 N transport in intact barley roots (Fig.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…This study critically reexamines the nature of futile transmembrane NH 3 /NH 4 + cycling in barley roots, a phenomenon with ties to NH 4 + toxicity in a wide range of higher plants (Feng et al, 1994;Britto et al, 2001bChen et al, 2013 ; Fig. 1A), electroneutral NH 3 transport accounts for the observed rapid rates of 13 N transport in intact barley roots (Fig.…”
Section: Discussionmentioning
confidence: 82%
“…In this model, a rapid, thermodynamically passive influx of NH 4 + is coupled to an active efflux of NH 4 + that is nearly as rapid, constraining normal cellular function and energetics and resulting in plant growth decline and mortality. This phenomenon is thought to occur in NH 4 + -sensitive species such as barley (Hordeum vulgare) and, to a lesser extent, in tolerant species such as rice (Oryza sativa), which can be susceptible at higher thresholds (Balkos et al, 2010;Chen et al, 2013).…”
mentioning
confidence: 99%
“…Ammonium uptake is highly regulated by NH 4 + transporters (Loque and von Wiren, 2004). Plant species vary in their sensitivity to NH 4 + nutrition (Britto and Kronzucker, 2002;Dowling 1993;Bremner and Krogmeier, 1989), and genotypic variation within a species such as rice (Oryza sativa L.) has also been observed (Chen et al, 2013). Yet, some species variation in radicle vs. coleoptile sensitivity to NH 3 was not correlated to their germination sensitivity to NH 3 (Dowling, 1993).…”
mentioning
confidence: 99%
“…Many studies on genetic variation for NUE in various crops reported large interactions between genotype and N stress and other environmental conditions (Cabrera-Bosquet et al 2007, Anbessa et al 2009, Beatty et al 2010, Wei et al 2012, Chen et al 2013). The investigations of Bouchet et al (2014), using an oilseed rape mapping population are a good example of such studies in which they determined genomic regions (Quantitative Trait Loci (QTLs)) associated with yield and assessed their stability under contrasting nitrogen nutrition regimes.…”
Section: Screening Methodologies For Nuementioning
confidence: 99%
“…The definition of NUE applied in this study is the yield produced per unit of added N (Dresbøll and Thorup-Kristensen 2014). NUE is already an important target for breeding research in many crops such as wheat (Cabrera-Bosquet et al 2007), barley (Anbessa et al 2009, Beatty et al 2010, rice (Wei et al 2012, Chen et al 2013, and oilseed rape (Koeslin-Findeklee et al 2014).…”
Section: Introductionmentioning
confidence: 99%